The Application of ISAK 335 in the Preparation of Istiqomah Mosque Financial Statements Using Appsheets - Wira Andi Saputra; Husnul Muttaqin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study is driven by the fact that the Istiqomah Mosque still manages its financial records in a simple manner using Excel, only documenting cash receipts and disbursements, which means the reporting process has not yet aligned with the non-profit financial reporting standards set out in ISAK 335. The study aims to evaluate how far the mosque’s financial reporting meets ISAK 335 requirements, outline the procedures for preparing proper reports using the AppSheet application, and identify both the challenges and advantages of applying this system. A descriptive qualitative method was employed, with data collected through interviews, on-site observations, and document reviews, supported by primary information from mosque administrators and secondary data such as financial archives and relevant literature. The findings indicate that the mosque has not yet classified revenues and expenses based on donor restrictions and continues to produce basic reports focused solely on cash movements without a complete financial reporting structure. After adjustments were made using AppSheet, the mosque was able to compile statements of financial position, statements of comprehensive income, reports on changes in net assets, cash flow statements, and notes to financial statements in accordance with ISAK 335. The study concludes by recommending consistent implementation and ongoing development of the reporting system.